Formulasi hand cream antibakteri berbasis kitosan dan ekstrak daun putri malu (Mimosa pudica L.) - Fendy, Fendy; Suryawan, Chinesia Prastialin; Fadila, Rina Fitriana; M.Saad, Nabilatul Rafi’ah; Mubayyinah, Hamidatul; Darmawan, Noviyan (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
CoronaVirus Disease 2019 is a respiratory disease caused by Severe Acute Respiratory Syndrome CoronaVirus 2 (SARS-CoV-2) which is transmitted through the air and droplets of fluid. One of the health protocols recommended by the World Health Organization (WHO) is washing hands. Hand-washing activities have limitations because not all places provide them, so the alternative that has been circulating in the community is hand sanitiser. However, the alcohol content and synthetic antibacterials cause dry and irritated skin. The purpose of this study was to create an antibacterial hand cream from putri malu leaf as a utilization of wild plants. Putri malu leaf extract and chitosan were made in the form of nanoparticles, and then an evaluation of the physical characteristics of the hand cream preparation was carried out in the form of pH, organoleptic, homogeneity, and stability observed for 14 days. The antibacterial activity of putri malu leaf extract and hand cream was tested against S. aureus and E. coli. The particle size obtained was 1529.5 ± 42.5 nm. The results of the physical characteristics obtained were pH 6.15; dark orange, odourless, stable at room temperature, and high homogeneity. Antibacterial testing of putri malu leaf extract against S. aureus produced an inhibition zone of 10.27 mm at a concentration of 25% and antibacterial hand cream produced inhibition zones of 23.18 mm and 12.22 mm with an extract concentration of 10% so both are classified as strong antibacterials that are effective against S. aureus and E. coli bacteria.